PENGARUHPENAMBAHAN PUPUK HAYATI CAIR DENGANDOSIS BERBEDA TERHADAP KELANGSUNGAN HIDUP BENIH IKAN LELE (Clarias sp.) - dony hasudungan; ade dwi sasanti; ferdinand taqwa (Jurnal Akuakultur Rawa Indonesia, 2015)
ABSTRACT Biofertilizer is a material derived from living organism, particularly microbes, which are used to improve the quality and quantity of growing media and plants. In this case is a liquid biofertilizer that is derived from living organism and refers to the results of microbiological processes. Fertilization activities in the field of fisheries is done to help the maintenance media as ground pond in providing nutrients directly to the fertility of the pond. One of the microbes that exist in liquid biofertilizer is Bacillus sp.. Bacillus sp. can maintain stable water quality by reducing excess amonia concentration on the media. This research was conducted in December 2014 to January 2015 at Laboratorium Budidaya Perairan, Program Studi Akuakultur,Fakultas Pertanian, Universitas Sriwijaya, Inderalaya. This research was conducted using CRD (completely randomized design) is seven treatments of biofertilizer additions with three replications. Based on observations during the research, concluded that the addition of biofertilizer did not significantly affect the viability of the seeds of catfish fry that needs to be done further research on the mechanism of action of biofertilizer is working to help the fertility of the soil or water of the pool maintenance media or to both. Keywords :biofertilizer, catfish fry, survival rate